NILAI-NILAI PENDIDIKAN KARAKTER DARI KEHIDUPAN MULTIETNIS DI KESULTANAN SUMBAWA - Kasimanuddin Ismain (Universitas Negeri Malang, 2019)
In this democratic era, the ethnic advancement of a nation or region in Indonesia is like a double-edged knife, it can be both rich and prone to conflict. For this reason, it is necessary to develop a tolerant attitude in togetherness, through excavation of sources of tolerance as a reference. This research uses the historical method including the stages of heuristics, criticism, interpretation, and historiography. Heuristics and criticism were carried out on historical sources obtained in Makassar, Mataram and Sumbawa Besar. It turned out that the leading factor in the Sultan as a role model, as well as accepting and granting land for settlement to each ethnic migrant, including making the church as a means of worship. The Sultan's example also represented a tolerant attitude that was always open to accepting and living in harmony with ethnic migrants. The history of the Sumbawa Sultanate, found the values of character education as local wisdom which is very valuable to foster tolerance and togetherness. The values of character education are none other than universal values in Pancasila. The present generation learns history and learns from the history of previous generations. Character education remains a priority in the field of education development in Indonesia.Di era demokrasi ini, kemajukan etnis suatu bangsa atau daerah di Indonesia bagaikan pisau bermata dua, bisa menjadi kekayaan sekaligus rentan konflik. Untuk itu perlu terus dibina sikap toleran dalam kebersamaan, melalui penggalian sumber-sumber toleransi sebagai rujukan. Penelitian ini menggunakan metode sejarah meliputi tahap-tahap heuristik, kritik, interpretasi, dan historiografi. Heuristik dan kritik dilakukan pada sumber-sumber sejarah yang diperoleh di Makasar, Mataram dan Sumbawa Besar. Ternyata faktor kepemimpinan pada diri Sultan sebagai teladan, sebagaimana menerima dan menghibahkan tanah untuk pemukiman kepada setiap etnis pendatang, termasuk membuat gereja sebagai sarana beribadah. Keteladanan sultan juga merepesentasikan sikap toleran yang senantiasa terbuka menerima dan hidup harmonis dengan etnis pendatang contoh. Dari sejarah Kesultanan Sumbawa, ditemukan nilai-nilai pendidikan karakter sebagai kearifan lokal yang sangat berharga untuk memupuk toleransi dan kebersamaan. Nilai-nilai pendidikan karakter itu tidak lain dari nilai-nilai unversal dalam Pancasila. Generasi sekarang belajar sejarah dan belajar dari sejarah generasi terdahulu. Pendidikan karakter tetap menjadi prioritas pembangunan bidang pendidikan di Indonesia. <w:LsdException Locked=